Managing brands and customer engagement in online brand communities - Wirtz, J.; Ramaseshan, Balasubramanian; van de Klundert, J.; Canli, Z.; Kandampully, J. (Emerald Group Publishing Limited, 2013)
Purpose: Given the dramatic technology-led changes that continue to take place in the marketplace, researchers and practitioners alike are keen to understand the emergence and implications of online brand communities (OBCs). The purpose of this paper is to explore OBCs from both consumer and company perspectives. Design/methodology/approach: The study provides a synthesis of the extant OBC literature to further our understanding of OBCs, and also puts forth future priorities for OBC research. Findings: A conceptual framework is provided that extends our understanding of OBCs and consumer engagement. Four key OBC dimensions (brand orientation, internet-use, funding and governance) are identified and three antecedents (brand-related, social and functional) are proposed of consumer-OBC engagement. Originality/value: This study is the first to explore key dimensions of OBCs, and the differing but related perspectives of the consumers and organizations involved.